Ability of an avirulent mutant of Vibrio cholerae to colonize in the infant mouse upper bowel. - Sigel, S P (1981)
Vibrio cholerae strain 3083 (biotype El Tor, serotype Ogawa) and Texas Star-SR (SR), a mutant derived from 3083 that produces the B (binding) but not the A (toxic) subunit of choleragen, were compared in their abilities to: (i) associate with the infant mouse upper bowel; (ii) survive and multiple there; and (iii) induce diarrhea. Vibrios labeled with 35SO4 were used to determine association with the upper bowel and ability to multiply. The parental strain associated significantly better than SR, although viable mutant cells were found in the infant mouse intestine 16 to 18 h after challenge. Addition of exogenous toxin enhanced the rate at which labeled SR (but not 3083) was cleared, further suggesting that SR associates less well with the upper bowel. Both SR and 3083 multiplied in the upper bowel but, due perhaps to slight net killing during the first 3 h and its more rapid rate of clearance, SR achieved a population size only 10% that of 3083 by 8 h postchallenge. Strain 3083 elicited diarrhea in infant mice but SR did not, even after 10 successive passages through the infant mouse intestine. Strain SR was slightly temperature sensitive at 37 and 40 degrees C. Its potential use as a live vaccine is discussed.